Diagnostics and updated catalogue of Acalyptris Meyrick, the second largest genus of Nepticulidae (Lepidoptera) in the Americas - Stonis, Jonas R.; Diškus, Arūnas; Diškus, Arūnas; Remeikis, Andrius; Vargas, Sergio A.; Solis, M. Alma (Zootaxa, 2020)
We list all 56 currently known Acalyptris Meyrick species from North and South America, designate five new species groups, and provide pictorial diagnostics for all nine revised species groups of the American fauna. We describe seven new species: A. marmor Stonis & Diškus, sp. nov., A. barbudo Stonis & Remeikis, sp. nov., A. jareki Stonis & Diškus, sp. nov., A. hilli Stonis & Diškus, sp. nov., A. mortalis Diškus & Stonis, sp. nov., A. hyacinthum Stonis & Vargas, sp. nov., and A. extremus Stonis & Diškus, sp. nov. We provide new data on morphology, biology or distribution for the following species: A. murex Diškus & Stonis, A. hispidus Puplesis & Robinson, A. trifidus Puplesis & Robinson, A. bifidus Puplesis & Robinson, A. terrificus Šimkevičiūtė & Stonis, and particularly A. yucatani Remeikis & Stonis. We transfer Fomoria miranda Diškus & Stonis to Acalyptris and provide the first photographic documentation of A. novenarius Puplesis & Robinson, A. fortis Puplesis & Robinson, A. martinheringi Puplesis & Robinson, A. basihastatus Puplesis & Diškus, A. pseudohastatus Puplesis & Diškus, A. articulosus Puplesis & Diškus, A. bovicorneus Puplesis & Diškus, and A. insolentis Puplesis & Diškus. We also comment on the re-deposition of some type series to the collection of the Zoological Museum of the Natural History Museum of Denmark, Copenhagen.